2012
DOI: 10.35652/igjps.2012.26
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Knowledge on Medicinal Non-Timber Forest Products(NTFP) in Parbat District of Nepal

Abstract: Present study aims to focus on the hidden indigenous knowledge on medicinal non- timber forest products (NTFP) among the four ethnic tribes (Gurung, Magar, Kumal and Majhi) of Parbat district. NTFP are being collected from the different areas of the local forests. Ethnobotanical investigation has been carried out to accumulate traditional knowledge on the use of 28 species of plants belonging to 27 genera under 22 families. Relative reliability index (RRI) has been calculated for rating different plant species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…According to Vogl et al (2016), farmers in Eastern Tyrol (Austria) have extensive knowledge of fodder species and their applications for livestock health. Malla and Chhetri (2012) reported that ethnic people in Nepal's Parbat district used 21 plants in ethnoveterinary practices. These findings are consistent with our findings in this study.…”
Section: Discussionmentioning
confidence: 99%
“…According to Vogl et al (2016), farmers in Eastern Tyrol (Austria) have extensive knowledge of fodder species and their applications for livestock health. Malla and Chhetri (2012) reported that ethnic people in Nepal's Parbat district used 21 plants in ethnoveterinary practices. These findings are consistent with our findings in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In ethnomedicinal studies, FIC analysis gives a measure of accessibility for the given information of data collection (59). In this study, the medicinal plants used to cure various ailments in the Sivasagar District of Assam were classified into 17 ICPC (International Classification of Primary Care) (https://www.who.int/standards/classifications/otherclassification/international-classification-of-primary-care)…”
Section: Informant Consensus Factor (Fic)mentioning
confidence: 99%
“…This could be because the studied community is dominated by a single ethnic group (Tamang) and suggested that the ethnomedicinal uses of plants are currently in practice in the study area. The factor of informant consensus provides a measure of reliability for the given claim of evidence in the ethnomedicinal studies (Malla & Chhetri 2012). The higher level of consensus about the use of particular taxa for curing ailments indicates ethnomedicinal use of plants is in practice (Singh et al 2012.…”
Section: Informant Consensus Factor (Icf)mentioning
confidence: 99%